The Prognostic Impact of Intratumoral Aryl Hydrocarbon Receptor in Primary Breast Cancer Depends on the Type of Endocrine Therapy: A Population-Based Cohort Study - Tryggvadottir, Helga; Sandén, Emma; Björner, Sofie; Bressan, Alessandra; Ygland Rödström, Maria; Khazaei, Somayeh; Edwards, Dean P.; Nodin, Björn; Jirström, Karin; Isaksson, Karolin; Borgquist, Signe; Jernström, Helena (Frontiers in Oncology, 2021)
The aryl hydrocarbon receptor (AhR) is a master regulator of multiple pathways involved in breast cancer, and influences the estrogen receptor alpha (ER) and aromatase/CYP19A1. The purpose of this study was to elucidate the interplay between intratumoral levels of AhR and aromatase, patient characteristics (including AhR and CYP19A1 genotypes), clinicopathological features, and prognosis in breast cancer patients receiving adjuvant treatments. A prospective cohort of 1116 patients with primary breast cancer in Sweden, included 2002–2012, was followed until June 30th 2019 (median 8.7 years). Tumor‐specific AhR (n=920) and aromatase levels (n=816) were evaluated on tissue microarrays using immunohistochemistry. Associations between cytoplasmatic (AhRcyt) and nuclear (AhRnuc) AhR levels, intratumoral aromatase, clinicopathological features, and prognosis in different treatment groups were analyzed. Low AhRcyt levels (n=183) and positive intratumoral aromatase (n=69) were associated with estrogen receptor (ER)– status and more aggressive tumors. Genotypes were not associated with their respective protein levels. The functional AhRArg554Lys GG genotype was associated with recurrence-free survival in switch-therapy (sequential tamoxifen/aromatase inhibitors (AI) or AI/tamoxifen) treated patients (HRadj 0.42; 95% CI 0.22–0.83). High AhRcyt levels were associated with longer recurrence-free survival during the first 10 years of follow-up among tamoxifen-only treated patients (HRadj 0.40; 95% CI 0.23–0.71) compared to low AhRcyt levels, whereas an almost inverse association was seen in patients with switch-therapy (Pinteraction=0.023). Intratumoral aromatase had little prognostic impact. These findings warrant confirmation in an independent cohort, preferably in a randomized clinical trial comparing different endocrine regimens. They might also guide the selection of breast cancer patients for clinical trials with selective AhR modulators.